Comparison of practical and metaphysical approaches to the problem of personal identity in analytic philosophy (Actual Problems of Mind, 2023)
Abstract. The paper considers the problem of personal identity in analytic philosophy, which is a question of why a person remains identical to themselves over time, and what personal identity grounds on. In analytic philosophy, the problem of personal identity is usually considered in metaphysics. However, as Derek Parfit has shown,  the problem of personal identity is not what matters in metaphysics. He suggests that it should be revised in ethics. Due to his influential works, the problem of personal identity starts being considered in practical philosophy. Since the 1980s, analytic philosophers have been developing two approaches to the mentioned problem. The first approach is the normative one. According to it, personal identity turns a human being into a moral agent. Without identity, an individual cannot become a person at all. The other approach is narrative one, which explains that a person combines different experiences into a narrative, and that is the way for a person to remain the same over time. Despite the differences between the two approaches, they both base on the same conceptual model – the notion of practical identity. In this paper, we suggest that narrative and normative theories of personal identity should be viewed within the practical approach to the problem, which opposes the metaphysical approach. This article outlines the key ideas of the practical approach to personal identity and compares it to personal identity in metaphysics. These three key points are the understanding of the notion of a person, the interpretation of identity and the way to consider the problem of identity criterion or criteria. In the practical approach to identity, a person is an agent. Identity is viewed through the concept of the attribution of actions. Personal identity consists of the unity of one’s self. The question of personal identity criteria becomes a question of reidentification. Personal identity is based not on criterion but on the mechanism of action attribution. As compared to the understanding of personal identity in metaphysics, the practical way to consider it highlights that identity is a process of keeping the unity of one’s self over time using action attribution.
Keywords: agent; attribution of action; personal identity; practical identity; personal identity criterion; analytic philosophy